Strangers to peace [videorecording (DVD)] - Angel, Laura (Freestyle Digital Media, 2023)
Three former child soldiers face retribution, anxiety, and danger as they attempt to rebuild their lives after fighting in Colombia's bloody civil conflict. Can these former guerrilla fighters, seen by society as terrorists, redefine their futures?